Valproic Acid Addresses Neuroendocrine Differentiation of LNCaP Cells and Maintains Cell Survival - Giordano F; Naimo GD; Nigro A; Romeo F; Paolì A; De Amicis F; Vivacqua A; Morelli C; Mauro L; Panno ML (Dove Medical Press, 2019)
Francesca Giordano,1 Giuseppina Daniela Naimo,1 Alessandra Nigro,1 Francesco Romeo,2 Alessandro Paolì,1 Francesca De Amicis,1 Adele Vivacqua,1 Catia Morelli,1 Loredana Mauro,1 Maria Luisa Panno1 1Department of Pharmacy, Health and Nutritional Sciences, University of Calabria, Cosenza 87036, Italy; 2Pathologic Anatomy Unit, Annunziata Hospital, Cosenza, ItalyCorrespondence: Maria Luisa PannoDepartment of Pharmacy and Health and Nutrition Sciences, University of Calabria, Rende, Cosenza 87036, ItalyTel +39 984 492927Email mamissina@yahoo.itPurpose: Neuroendocrine differentiation of prostate cancer, induced by androgen deprivation therapy, is mainly related to advanced disease and poor clinical outcome. Genetic and epigenetic alterations are the key elements of the prostate carcinogenesis. A group of compounds able to induce changes in this sense is inhibitors of histone deacetylase, to which it belongs valproic acid (VPA). In the present paper, we evaluated the role of this molecule on the neuroendocrine differentiation of LNCaP cells together with the effect on proliferation and survival signals.Methods: Cell growth was analyzed by MTT and flow cytometry, while expression of proteins through Western blot analysis.Results: Our results have documented that VPA in LNCaP cells reduces cell proliferation, decreases the S phase and Cyclin A, and up-regulates the cyclin-dependent kinase inhibitors p21waf and p27. The acquisition of androgen-independent condition is consistent with an induction of β-III Tubulin and gamma Enolase, both markers of neuroendocrine phenotype. However, all these features cease with the removal of valproate from the culture medium, demonstrating the transitory nature of the epigenetic event. The VPA treatment does not compromise the survival phosphorylated signals of Akt, ERK1/2 and mTOR/p70S6K that remain up-regulated. Consistently, there is an increase of phospho-FOXO3a, to which corresponds the decreased expression of the corresponding oncosuppressor protein.Conclusion: Overall, our findings indicate that VPA in LNCaP prostate tumor cells, although it reduces cell proliferation, is able to drive neuroendocrine phenotype and to maintain the survival of these cells. Keeping in mind that neuroendocrine differentiation of prostate cancer appears to be associated with a poor prognosis, it is necessary to develop new treatments that do not induce neurodifferentiation but able to counteract cell survival.Keywords: prostate cancer, cell proliferation, cell cycle, neuroendocrine tumor